THE INFLUENCE OF SERVICE FEATURES, TRANSACTION SECURITY, BRAND AMBASSADORS AND PERCEIVED EASE OF USE ON BANK BRI CUSTOMER DECISIONS USING THE BRIMO APPLICATION - Nur Cahyo , Dwi; Sutarso , Yudi (JURNAL EKBIS, 2024)
The purpose of this study was to examine the effect of service features, transaction security, brand ambassadors and perceived convenience on customer decisions using the BRImo application. This study uses quantitative research methods. The population in this study were BRI customers who opened savings accounts at BRI KCP Sudiang from January to June 2023 totaling 15,850 people, the sampling technique used in the study was structured data collection using the Slovin formula. So the sample in this study was a total of 98 respondents. The data analysis technique in this study used multiple linear regression analysis. The results showed that service features have a significant effect on customer decisions using the BRImo application. Transaction security has a significant effect on customer decisions using the BRImo application. Brand ambassadors have an insignificant effect on customer decisions using the BRImo application. Perceived ease of using the product has a significant effect on customer decisions using the BRImo application.